BETEL LEAF OIL AS A NATURAL DISINFECTION AGENT IN RADIOLOGICAL EQUIPMENT (STUDY OF MICROBIAL QUANTITY OF RADIOGRAPHIC CASSETTE) - Saifudin; Isnoviasih, Susi Tri; Kurniawan, Andrey Nino; Amalia, Rizki (Journal of Vocational Health Studies, 2023)
Background: Betel leaf oil is a wonderful natural antiseptic. Betel leaf oil is rich in polyphenols, especially chavicol, which can be used to protect against microbe pathogens that cause infection. The cause of the spread of nosocomial infections in radiology can occur using a radiographic cassette. Previous research has found that radiographic cassette contains microorganisms and fungi. Purpose: To determine the effectiveness of using betel leaf oil as a natural disinfection on a radiographic cassette. Method: Quasi-experimental research with pre-test and post-test design designs was carried out by calculating the number of microbes, including Total Plate Count (TPC), Staphylococcus, and fungi. The study on 12 conventional radiographic cassettes was calculated using the swab method before and after cleaning with betel leaf oil. The data were analyzed descriptively to illustrate the rate of decline. Result: The results showed that the percentage rate of decline after the radiographic cassette was cleaned with betel leaf oil was ALT (17.8%), Staphylococcus (57.41%), and fungi (37.21%). Conclusion: Betel leaf oil can be used as alternative natural disinfection on radiographic cassettes, quite effectively suppressing the activity and number of microbes present.